The fictitious domain method for the Stokes problem with Neumann/free-traction boundary condition - Zhou, Guanyu (Japan journal of industrial and applied mathematics, 2017)
We consider the fictitious domain method for the Stokes problem with Neumann/free-traction boundary condition. For the penalty method, we obtain the error estimate of order O ( ϵ ) , where ϵ is the penalty parameter. Next, we apply the finite element method to the penalty problem using the P1/P1 element with stabilization, and obtain the error estimate of discretization. The theoretical results are verified by the numerical experiments.